Implementation Analysis of the Village Council Function in Donowarih Village Administration, Malang Regency - Mariano Werenfridus; Zainul Rahman; Krishno Hadi (Universitas Medan Area, 2021)
Implementation of the functions of The Village Government (BPD) had a major role in achieving the performance of governance in the village. The effectiveness in carrying out the functions was determined by the synchronization related to the factors such as supervision, policy-making, and delivery of the aspirations of the people. To answer this, the study was intended to analyze the implementation of the function of BPD in Donowarih Village by using qualitative approach-based software with tools of the analysis Nvivo. Data coleection was obtained through observation, interviews with relevant stakeholders, and the study of literature. The stages of analysis was conducted by using Nvivo begins with an assessment of the three functions of BPD as embodied in Article 55 of Law No. 6 of 2014 about the Village. The results of this research showed that implementation of the functions of BPD in Donowarih Village was less effective caused by several factors, among others: the composition of human resources, facilities support activities of BPD, the differentiation of the major work of each member of the BPD, and the lack of benefits received by BPD members. Therefore, implementation of the function of BPD in Donowarih Village was less than the maximum due to such factors greatly affecting the performance of the glittering efforts of governance in the Donowarih Village.